Effects of Elevated Crude Glycerin Concentrations on Feedlot Performance and Carcass Characteristics in Finishing Steers - Chanjula, P. (Asian-Australas J Anim Sci, 2016)
Twenty crossbred steers (400±40.1 kg of initial body weight) were used to assess the effects of a dietary supplementation with crude glycerin (CG) as a substitute for corn grain on performance, carcass traits, and meat quality. Four isocaloric and isonitrogenous diets were offered to the experimental animals (5 steers per treatment) for 121 days using randomized complete block design. The steers individually received dietary treatments containing 0%, 7%, 14%, and 21% of CG (88.91% pure) on a dry matter (DM) basis. The diets were offered ad libitum as total mixed rations twice daily. Weight gain and carcass traits were determined. At the end of the experimental period, the harvest data and carcass characteristics of the steers were recorded, and meat quality was determined. No significant effect of CG inclusion was observed in any of the growth performance and carcass characteristics traits studied. Also, there were no apparent effects of diets (p>0.05) on meat quality (pH, water holding capacity, drip losses, and cooking losses). The study concluded that CG could be used as a substitute for corn grain up to the level of approximately 21% of DM in the diets of finishing steers.